EEPD1 Is a Novel LXR Target Gene in Macrophages Which Regulates ABCA1 Abundance and Cholesterol Efflux. Issue 3 (March 2017) - Nelson, Jessica Kristine; Koenis, Duco Steven; Scheij, Saskia; Cook, Emma Clare Laura; Moeton, Martina; Santos, Ana; Lobaccaro, Jean-Marc Adolphe; Baron, Silvere; Zelcer, Noam
Abstract : Objective—: The sterol-responsive nuclear receptors, liver X receptors α (LXRα, NR1H3 ) and β (LXRβ, NR1H2 ), are key determinants of cellular cholesterol homeostasis. LXRs are activated under conditions of high cellular sterol load and induce expression of the cholesterol efflux transporters ABCA1 and ABCG1 to promote efflux of excess cellular cholesterol. However, the full set of genes that contribute to LXR-stimulated cholesterol efflux is unknown, and their identification is the objective of this study. Approach and Results—: We systematically compared the global transcriptional response of macrophages to distinct classes of LXR ligands. This allowed us to identify both common and ligand-specific transcriptional responses in macrophages. Among these, we identified endonuclease–exonuclease–phosphatase family domain containing 1 ( EEPD1/KIAA1706 ) as a direct transcriptional target of LXRs in human and murine macrophages. EEPD1 specifically localizes to the plasma membrane owing to the presence of a myristoylation site in its N terminus. Accordingly, the first 10 amino acids of EEPD1 are sufficient to confer plasma membrane localization in the context of a chimeric protein with GFP. Functionally, we report that silencing expression of EEPD1 blunts maximal LXR-stimulated Apo AI-dependent efflux and demonstrate that this is the result of reduced abundance of ABCA1 protein in human and murine macrophages. Conclusions—: In this study, we identify EEPD1 as a novel LXR-regulated gene in macrophages and propose that it promotes cellular cholesterol efflux by controlling cellular levels and activity of ABCA1. Abstract : Supplemental Digital Content is available in the text.